Ṣaḍdarśanam : sūtra aura Hindī-anuvāda - Jagadīśvarānanda Sarasvatī, Swami (Govindarāma Hāsānanda, 1979)
Six basic texts of the orthodox Hindu philosophy; with interpretations according to the Arya Samaj tradition.